1981
DOI: 10.1037/0022-006x.49.5.633
|View full text |Cite
|
Sign up to set email alerts
|

A competency-based parent training program for child abusers.

Abstract: An intervention program for child abusers was evaluated using multiple outcome criteria and extended follow-up. Families were assigned to treatment (n = 8) and control (n = 8) groups on a first-come basis. All families were supervised by protective services, and none had requested help voluntarily. A treatment program involving group parent training in the clinic and competency-based training and rehearsal in the home was provided. The findings indicated that training abusive parents in child-management and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(44 citation statements)
references
References 16 publications
0
43
0
1
Order By: Relevance
“…The content of the programs was reasonably similar, with a shared focus on teaching and practicing parenting skills and child management strategies to break cycles of coerciveness in parent–child interaction, although some programs also included modules on child health and safety practices (e.g., Chaffin et al 2012). While most programs ran weekly sessions with a similar duration (between 1 and 2 h per session), the total duration of each program varied greatly, with 6 of the programs running for 4–8 months (Chaffin et al 2004, 2011, 2012; Terao 1999; Jouriles et al 2010; Mast et al 2014; Kolko 1996; Runyon et al 2010), some running for only 8 weeks (Hughes and Gottlieb 2004; Swenson et al 2010; Egan 1983; Brunk et al 1987; Wolfe et al 1981), and one for over 2 years (MacMillan et al 2005). Programs were delivered either individually, to groups, or both; and fully or partially delivered in the home (Jouriles et al 2010; Kolko 1996; MacMillan et al 2005; Wolfe et al 1981; Terao 1999), healthcare or other clinics (Chaffin et al 2004, 2011; Brunk et al 1987, Kolko 1996, Wolfe et al 1981, Runyon et al 2010), community centers (Chaffin et al 2012, Hughes and Gottlieb 2004, Swenson et al 2010), and online (Mast et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The content of the programs was reasonably similar, with a shared focus on teaching and practicing parenting skills and child management strategies to break cycles of coerciveness in parent–child interaction, although some programs also included modules on child health and safety practices (e.g., Chaffin et al 2012). While most programs ran weekly sessions with a similar duration (between 1 and 2 h per session), the total duration of each program varied greatly, with 6 of the programs running for 4–8 months (Chaffin et al 2004, 2011, 2012; Terao 1999; Jouriles et al 2010; Mast et al 2014; Kolko 1996; Runyon et al 2010), some running for only 8 weeks (Hughes and Gottlieb 2004; Swenson et al 2010; Egan 1983; Brunk et al 1987; Wolfe et al 1981), and one for over 2 years (MacMillan et al 2005). Programs were delivered either individually, to groups, or both; and fully or partially delivered in the home (Jouriles et al 2010; Kolko 1996; MacMillan et al 2005; Wolfe et al 1981; Terao 1999), healthcare or other clinics (Chaffin et al 2004, 2011; Brunk et al 1987, Kolko 1996, Wolfe et al 1981, Runyon et al 2010), community centers (Chaffin et al 2012, Hughes and Gottlieb 2004, Swenson et al 2010), and online (Mast et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Previous treatment outcome studies have shown the ECBI to be a sensitive measure of change in conduct problem behaviors of children (Eyberg & Matarazzo, 1980;Eyberg & Robinson, 1982;Webster-Stratton, 1982;Wolfe, Sandier, & Kaufman, 1981). The marked differences obtained between conduct problem and normal adolescents in this study suggest that the ECBI may be a sensitive instrument for measuring change in adolescent treatment as well.…”
Section: Discussionmentioning
confidence: 66%
“…The scores have been found to relate significantly to direct observational measures of parent-child interactions, activity level, and temperament (Robinson & Eyberg, 1981;Webster-Stratton & Eyberg, 1982). The ECBI has been shown to be sensitive to treatment eff'ects of parent training programs (Eyberg & Robinson, 1982;Packard, Robinson, & Grove, 1983;Webster-Stratton, 1982, 1984Wolfe, Sandler, & Kaufman, 1981).…”
Section: Measures Of Treatment Outcome In the Primary Settingmentioning
confidence: 96%